Role of education and work experience in journalists’ perception about journalism codes of ethics - Motlagh, Nafise Esmael; Hassan, Md. Salleh; Bolong, Jusang; Osman, Mohd Nizam (Asian Economic and Social Society, 2013)
This study examines the role of work experience and education in ethical perception of Malaysian journalists (N =231). Results show that there is big numbers of journalists (more than half of the respondents) who have unfavourable attitude towards journalism codes of ethics. They believe that journalism codes of ethics do not decrease the journalist’s mistakes effectively, and cannot be formulated in a certain canon or principals. Meanwhile majority of them think journalists can use any method or technique to obtain news if it is essentially important for public including unfair methods like hidden camera and hidden voice recorder. However, the results shows, there is no significant difference between ethical perception of journalists who studied journalism/ media and those who did not. While there is a significant correlation between journalists’ ethical perception and their work experience; the more experience they have, the more favourable perception they have regarding to journalism codes of ethics.